Effect of Market Risk Premium and Exchange Rate#xA0;on#xA0;the#xA0;Return of#xA0;Jakarta Islamic Index (Global Journal of Management and Business Research, 2020)
Effect of Market Risk Premium and Exchange Rate on the Return of Jakarta Islamic Index. This study aims to analyze the effect of market risk premium and exchange rate on the return of Jakarta Islamic Index. By using the Vector Auto regression (VAR), this study utilizes time series monthly data from January 2008 to December 2018. This paper finds that the market risk premium has no significant effect on the return of Jakarta Islamic Index, while the exchange rate has a significant positive effect on the return of Jakarta Islamic Index. Shocks to market risk premium are responded negatively by return of Jakarta Islamic Index while shocks to exchange rate are responded positively by return of Jakarta Islamic Index
Keywords: market risk premium; exchange rate; return; jii; var